Descriptive features of modern social problems and global processes - Zoidze, Ineza; Lazba, Natalia (Politics / პოლიტიკა, 2020)
The article discusses some of the issues related to the socio-political and economic processes in the context of global processes and globalization at the modern stage. In particular, the analysis presents several directions of the problem: Globalization itself has gone a long way in terms of its content. Despite its scale and irreversibility, it is perceived as a multi-faceted process at the present stage. In the first half of 2020, developments in the world related to the pandemic process have revealed significant effects, especially in terms of social security. The irreversibility of globalization and the importance of its involvement were determined by the need to ensure economic security and the promotion of national cultures. In terms of social security, in our view, a number of contradictions have arisen. However, from a modern point of view, it can be said that in the long run, the global approach to these issues will be positive, as the processes of globalization will continue with new approaches and the principle of compatibility with existing challenges. The existing challenges will pave the way for the different manifestations of globalization processes, which will create another new stage in the history of its existence.
Keywords: Globalization; migration; social policy; social security; economy; pandemic